Earthquake Analysis Suggests Dyke Intrusion in 2019 Near Tarawera Volcano, New Zealand - Benson, Thomas W.; Illsley-Kemp, Finnigan; Elms, Hannah C.; Hamling, Ian J.; Savage, Martha K.; Wilson, Colin J. N.; Mestel, Eleanor R. H.; Barker, Simon J. (Frontiers in Earth Science, 2021)
Tarawera volcano (New Zealand) is volumetrically dominated by rhyolitic lavas and pyroclastic deposits, but the most recent event in AD 1886 was a basaltic plinian fissure eruption. In March 2019 a swarm of at least 64 earthquakes occurred to the NE of Tarawera volcano, as recorded by the New Zealand Geohazard Monitoring Network (GeoNet). We use seismological analysis to show that this swarm was most likely caused by a dyke intrusion that intruded into the brittle crust between depths of 8–10 km and propagated towards Tarawera volcano for 2 km at a rate of 0.3–0.6 m s$^{-1}$. We infer that this was a dyke of basaltic composition that was stress-guided towards Tarawera volcano by the topographic load of the volcanic edifice. A similar process may have occurred during the 1886 eruption with a dyke sourced from some lateral distance away from the volcano. The 2019 intrusion was not detected by InSAR geodesy and we use synthetic models to show that geodetic monitoring could only detect a >6 m wide dyke at these depths. Improvements to geodetic monitoring, combined with detailed seismological analysis, could better detect future magmatic intrusions in the region and serve to help assess ongoing changes in the magmatic system and the associated possibilities of a volcanic event.